2024
DOI: 10.4046/trd.2023.0028
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Inflammatory Biomarkers in Exhaled Breath Condensates in Respiratory Clinical Fields

Yong Jun Choi,
Min Jae Lee,
Min Kwang Byun
et al.

Abstract: Background: Exhaled condensates contain inflammatory biomarkers; however, their roles in the clinical field have been under-investigated.Methods: We prospectively enrolled subjects admitted to pulmonology clinics. We collected exhaled breath condensates (EBC) and analysed the levels of six and 12 biomarkers using conventional and multiplex enzyme-linked immunosorbent assay, respectively.Results: Among the 123 subjects, healthy controls constituted the largest group (81 participants; 65.9%), followed by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Certain molecules in exhaled breath are biomarkers and indicators of diseases. Recent analyses and studies have concluded that all humans generate a unique profile of volatile organic compounds (VOCs) in exhaled breath, which is a product of different metabolic activities in the human body [1][2][3]. Thus, any change in the VOC profile has the potential to confirm a particular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Certain molecules in exhaled breath are biomarkers and indicators of diseases. Recent analyses and studies have concluded that all humans generate a unique profile of volatile organic compounds (VOCs) in exhaled breath, which is a product of different metabolic activities in the human body [1][2][3]. Thus, any change in the VOC profile has the potential to confirm a particular disease.…”
Section: Introductionmentioning
confidence: 99%